Activation-induced cytidine deaminase localizes to G-quadruplex motifs at mutation hotspots in lymphoma. (13th October 2020) - Xu, Ying-Zhi; Jenjaroenpun, Piroon; Wongsurawat, Thidathip; Byrum, Stephanie D; Shponka, Volodymyr; Tannahill, David; Chavez, Elizabeth A; Hung, Stacy S; Steidl, Christian; Balasubramanian, Shankar; Rimsza, Lisa M; Kendrick, Samantha
Abstract: Diffuse large B-cell lymphoma (DLBCL) is a molecularly heterogeneous group of malignancies with frequent genetic abnormalities. G-quadruplex (G4) DNA structures may facilitate this genomic instability through association with activation-induced cytidine deaminase (AID), an antibody diversification enzyme implicated in mutation of oncogenes in B-cell lymphomas. Chromatin immunoprecipitation sequencing analyses in this study revealed that AID hotspots in both activated B cells and lymphoma cells in vitro were highly enriched for G4 elements. A representative set of these targeted sequences was validated for characteristic, stable G4 structure formation including previously unknown G4s in lymphoma-associated genes, CBFA2T3, SPIB, BCL6, HLA-DRB5 and MEF2C, along with the established BCL2 and MYC structures. Frequent genome-wide G4 formation was also detected for the first time in DLBCL patient-derived tissues using BG4, a structure-specific G4 antibody. Tumors with greater staining were more likely to have concurrent BCL2 and MYC oncogene amplification and BCL2 mutations. Ninety-seven percent of the BCL2 mutations occurred within G4 sites that overlapped with AID binding. G4 localization at sites of mutation, and within aggressive DLBCL tumors harboring amplified BCL2 and MYC, supports a role for G4 structures in events that lead to a loss of genomic integrity, a critical step in B-cell lymphomagenesis.